Oxygen-dependent oxidation of proteins in the pathogenesis of spleen injury caused by acute blood loss, complicated by ischema-reperfusion of the limb and the efficiency of their correction by carbacetam - I. V. Iavorska (Kazimierz Wielki University, 2020)
Activation of free radical processes is one of the key mechanisms of acute blood loss and ischemic-reperfusion syndrome. The spleen plays an important role in adaptive-compensatory processes during the blood loss. However, the state of oxidative modifications of proteins (OMP) in the spleen has not been studied enough. There are no data on the effectiveness of carbacetam in these conditions, that showed a pronounced protective effect on the enzyme link of the spleen antioxidant protection. Objective of research: to study the role of oxygen-dependent protein oxidation in the pathogenesis of spleen involvement during and after acute blood loss complicated by limb ischemia-reperfusion, and the effectiveness of its correction with carbacetam. Materials and methods. The experiments were performed on 108 nonlinear male rats weighing 200-220 g. All experiments were made using thiopental-sodium anesthesia. In separate groups of animals were simulated limb ischemia-reperfusion and acute blood loss as well as these combined injuries. In a separate group, the detected disorders were corrected with carbacetam. After 1 and 2 hours, as well as after 1, 7 and 14 days in the spleen of the experimental animals was determined the content of oxidative modifications of protein (OMP). The spleen was taken for additional investigation and the content of neutral (OMP370) and basic (OMP430) was determined in its homogenate. Results. Modeling of acute blood loss, complicated by ischemia-reperfusion of the limb, contributed to the increasing of the processes of uncontrolled oxidative modification of proteins in the spleen. The content of OMP370 rised significantly in the groups of animals, in which only ischemia-reperfusion of the limb or acute blood loss were simulated beginning from 2 h of the experiment. The content of OMP430 exceeded the base level in these experimental groups after 1 and 14 days. Violations of the studied indicators reached a maximum after 1 day, decreased to day 14, but did not reach the level of control group. Carbacetam had a protective effect on the intensity of OMP370-430 after 7 and 14 days of its usage, which puts carbacetam in a line of promising agents of complex therapy of spleen disturbances caused by acute blood loss and ischemic-reperfusion syndrome. Conclusions: Complication of acute blood loss by ischemia-reperfusion of the limb causes intensification of OMP in the spleen, that, compared with the control is an increase in the content of aldehyde and ketone derivatives of neutral and basic nature throughout the whole experiment with its maximal level at day 1. The use of carbacetam significantly reduces the intensity of OMP in the spleen compared to the group of animals that had no additional drug correction.